Determinants of intrauterine device use among reproductive-age women in a province implementing Islamic Sharia law in Indonesia: An application of the theory of planned behavior - Purnama, Dean R.; Dewi, Tgk. Puspa; Rusnaidi, Rusnaidi; Utami, Niken A.; Aditya, Rizka; Suhanda, Rachmad (Narra J, 2026)
The utilization of the intrauterine device (IUD) in Indonesia remains low at 3.9%, despite its high effectiveness (99.4%) and designation as a national family planning priority, suggesting the presence of psychosocial barriers influencing contraceptive behavior among women of reproductive age. This study aimed to analyze psychosocial factors influencing IUD use behavior based on the theory of planned behavior, including attitudes, subjective norms, perceived behavioral control, actual behavioral control, and intention, in Banda Aceh—the only province in Indonesia implementing holistic Sharia law. A quantitative cross-sectional study was conducted among women of reproductive age from six urban public health centers using cluster random sampling. Data were collected through face-to-face interviews using a structured TPB-based questionnaire validated for reliability. Statistical analyses included linear regression and binary logistic regression with a significance level set at p<0.05. A total of 442 women were included in the final analysis. Attitude toward IUD use, subjective norms, and perceived behavioral control were all significantly associated with intention to use an IUD, all had p<0.001. Attitudes toward IUD use (B=0.410; p<0.001; R²=0.213), subjective norms (B=0.552; p<0.001; R²=0.413), perceived behavioral control (B=0.273; p<0.001; R²=0.255), and actual behavioral control (B=0.273; p<0.001; R²=0.255) were all significantly associated with IUD use behavior. Intention to use an IUD emerged as the strongest predictor of IUD use behavior (B=0.780; p<0.001; R²=0.566). Intention to use an IUD emerged as the strongest predictor of IUD use behavior (B=0.78; p<0.001; R²=0.56). This study highlights that all intention was shaped by positive attitudes, strong subjective norms, and a high level of behavioral control. Efforts to increase IUD use should therefore focus on educational interventions, strengthening partner and social support, and improving the accessibility and quality of long-acting contraceptive services.